Socio-Political Consensus as a Foundation for Traffic Safety - Zagorc, Timotej Matej; Koritnik, Boštjan; Meško, Maja (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
The chapter examines speed cameras as a road safety measure whose significance extends beyond the mere technical detection of speeding violations. It is based on the understanding of traffic safety as a matter of public interest, requiring the integration of professional, technical-operational, and political perspectives while taking into account user experiences in the traffic environment. The aim of the chapter is to connect theoretical insights on traffic safety, social legitimacy, and public perception with empirical evidence on stakeholders’ views. The study is based on three semi-structured interviews with stakeholders representing technical, professional, and political domains. The findings indicate that speed cameras are more socially acceptable when they are professionally and data-driven justified, technically reliable, proportionate, and clearly communicated to the public. A particular risk arises when their road safety purpose becomes blurred and the measure is perceived primarily as a tool of punishment. The paper concludes that socio-political consensus is a key condition for the long-term effectiveness of road safety measures, as it links safety objectives, institutional responsibility, and public trust.